Draft Annual Plan 1988-89 Volume IV General Areas Government of Assam - Planning Commission (Planning Commission, 1988)
The backwardness of the State of Assam in respect of road Communication needs no elaboration. the present total Kilometerage of State roads in General areas is 22790. As per Master plan published by the Ministry of surface Transport for 1981—2001, Assam should have a total kilometerage of 85000 Kms. of roads of all categories by 2001 A.D. To achieve this target will call for manifold increase in the present level of investment in road development. There are many areas in the State particularly inhabited by Tribals and other Backward people where even after 40 years of Independence, no road Communication worth exists. Whatever road Communication the State has at present is deficient in many respects.
Government of Assam, Planning and Development Department